Transactional sex and HIV risk among adolescent schoolgirls in Ethiopia: Mixed method study - Dana, Liyuwork; Adinew, Yohannes Mehretie; Sisay, Mitike Molla (Hindawi Publishing Corporation, 2019)
Background. Young people in Sub-Saharan Africa are affected by HIV pandemic to a greater extent than elsewhere. Transactional sex among adolescent school girls with older men commonly called “sugar daddies” is one of the major factors fueling the spread of the infection due to the extended sexual network. Thus, this study aimed to assess the magnitude and factors associated with transactional sex among adolescent girls and “sugar daddies” in relation to HIV/AIDS. Methods. Mixed method cross-sectional study was done among 620 female students in Hawassa town, South Ethiopia, from September 2010 to May 2011. A structured questionnaire and in-depth interview check list were used to collect the quantitative and qualitative data, respectively. Survey participants were selected randomly from five preparatory schools whereas ten in-depth interview participants were recruited by a snowball sampling technique from the same schools. Data were entered using Epi-Info and analyzed by SPSS. A descriptive statistics followed by multivariable logistic regression analyses were conducted to identify factors associated with transactional sex with “sugar daddy’’. Both crude and adjusted odds ratios with 95% confidence interval were reported. We used OpenCode software for coding and categorizing the in-depth interviews and quotes that represent the informants opinion were used to support the quantitative findings. Results. A substantial number of female students, 71(11.5%), reported to have had transactional sex with older men. Most of the respondents who dated “sugar daddies” (93%) had multiple sexual partners concurrently and sequentially, and among them, only 22.7% had consistent condom use. Girls who were in older age group [OR (CI) 6.87 (3.48-13.58)], who had lost both parents [OR (CI) 2.99 (1.14-7.84)], had perceived less economic status [OR: 25.41; 95% CI: 7.80-82.76] and engaged in substance abuse [OR (CO) 5.8 (2.1-15.77)] had higher odds of practicing transactional sex with “sugar daddies”. In-depth interviewed participants also revealed that they were involved in transactional sex for monetary while having concurrent and subsequent sexual network with their schoolmates and other young partners. Conclusion. Transactional sex among female students was high, and the sexual network they had with the young men put young people in the network at risk of HIV and other sexually transmitted infections. Therefore, HIV prevention programs shall focus on transactional sex among adolescent school girls to halt transmission of HIV among the generation.